Higher Brain Perfusion May Not Support Memory Functions in Cognitively Normal Carriers of the ApoE ε4 Allele Compared to Non-Carriers - Zlatar, Zvinka Z.; Bischoff-Grethe, Amanda; Hays, Chelsea C.; Liu, Thomas T.; Meloy, M. J.; Rissman, Robert A.; Bondi, Mark W.; Wierenga, Christina E. (Frontiers in Aging Neuroscience, 2016)
Age-related changes in cerebral blood flow (CBF), which carries necessary nutrients to the brain, are associated with increased risk for mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Whether the association between CBF and cognition is moderated by apolipoprotein E (ApoE) ε4 genotype, a known risk factor for AD, remains understudied, with most research focusing on exploring brain regions in which there are diagnostic group differences in CBF (i.e., cognitively normal vs. MCI vs. AD). This study measured resting CBF via arterial spin labeling MRI and verbal memory functions using a composite score in 59 older adults with normal cognition (38 ε3; 21 ε4). Linear mixed effect models were employed to investigated if the voxel-wise relationship between verbal memory performance and resting CBF was modified by ApoE genotype. Results indicated that carriers of the ApoE ε4 allele display negative associations between verbal memory functions and CBF in medial frontal cortex, medial and lateral temporal cortex, parietal regions, insula, and the basal ganglia. Contrarily, ε3 carriers exhibited positive associations between verbal memory functions and CBF in medial frontal cortex, thalamus, insula, and basal ganglia. Findings suggest that higher CBF was associated with worse verbal memory functions in cognitively normal ε4 carriers, perhaps reflecting dysregulation within the neurovascular unit, which is no longer supportive of cognition. Results are discussed within the context of the vascular theory of AD risk.